1995
DOI: 10.1038/bjc.1995.29
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of DNA flow cytometry in breast cancer: results from 881 patients treated in a single centre

Abstract: S_q In this single-centre study of 881 patients, S-phase fraction (SPF) was shown to be a sgnifiant prognostic marker in terms of ovrll suvival (OS), rdapse-free survival (RFS) A further stimulus to publish our data came from two recent reports which failed to find a prognostic role for SPF in breast cancer (Stanton et al., 1992; Silvestini et al., 1993

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 25 publications
6
25
1
3
Order By: Relevance
“…Contradictory findings may result from differences in study design and technical, analytical and interpretative methods (15,(17)(18)(19)(20). Despite these limitations, the prognostic significance of DNA ploidy and SPF in breast cancer is relatively consensual, at least in univariate models (3,10,33). However, an important question remains in relation to the clinical utility and predictive value of DNA ploidy and SPF in the selection of adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contradictory findings may result from differences in study design and technical, analytical and interpretative methods (15,(17)(18)(19)(20). Despite these limitations, the prognostic significance of DNA ploidy and SPF in breast cancer is relatively consensual, at least in univariate models (3,10,33). However, an important question remains in relation to the clinical utility and predictive value of DNA ploidy and SPF in the selection of adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the evaluation of cytometric parameters can improve the management of breast cancer, aiding in the prognostic assessment and therapeutic planning for patients (2)(3)(4)(5)(6)9,10,24). The current study aimed to review the application of DNA flow cytometry in the prognostic assessment of patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow cytometric (FCM) S-phase fraction (SPF) is generally considered to be a prognostic factor in breast cancer (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In well-trained laboratories it has repeatedly been shown to be an independent prognostic factor, in both retrospective (6,8 -14) and prospective (7) investigations.…”
mentioning
confidence: 99%